Relationship between Family Knowledge and Prevention of Recurrent Stroke Attacks at the Neurological Polyclinic - Sari Wijayanti; MI Ekatrina Wijayanti; Thomas Aquino Erjinyuare Amigo (School of Health Sciences Al-Ma'arif, 2025)
Stroke is the most common neurological disorder where acute attacks can cause death in a short time or lifelong disability. Stroke patients have a risk of relapse or recurrent stroke. This study aims to determine the relationship between family knowledge and the prevention of recurrent stroke in the polyclinic of Santo Antonio Baturaja Hospital. This research is a type of quantitative research with a cross sectional design with accidental sampling technique, the population is 93 respondents on average every month with a sample using the Slovin formula totalling 75 respondents. In this study, the sample was a family who took care of their family members who suffered a stroke who visited the Santo Antonio Baturaja Hospital Polyclinic. Based on the results of the study, it is known that the level of family knowledge in the prevention of recurrent stroke has poor knowledge (53.3%). This is in line with the prevention of recurrent stroke attacks by the family in line with poor prevention (50.7%). The results of statistical analysis using the Spearman test showed a significant relationship between family knowledge and the prevention of recurrent stroke at the Santo Antonio Hospital polyclinic (pvalue=0.000) and r = 0.393. This study suggests optimising the role of the family in preventing recurrent stroke and providing extensive information on matters relating to advanced stroke disease and advanced stroke patient care at home